The Accompanying Text in The Syrian Play Script (Journal of Hama University, 2019)
In this study, we will try to shed light on some of the Syrian plays to highlight the most important features of the accompanying text in the Syrian theater. And, the extent of the use of the theater book, the role played by the aim of moving away from the traditional in dealing with the text of the Syrian theater and by focusing on the accompanying text (guidance play), which helps to understand the structure and interpretation of theatrical text and provide guidance on the stage, of the role  of the artistic and aesthetic work in theatrical work.